Commentary: Role of Micrornas in HIV Related Studies - Durairaj Sekar; Ramalingam Krishnan (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2015)
Micro RNAs (miRNAs) are well known regulatory factor of physiological and developmental processes, it has been revealed that many miRNAs contribute the initiation and progression of various cancers. Micro RNAs are being reported in body fluids, such as serum, plasma, and urine, and can be readily used as non-invasive biomarkers for various diseases and served as a novel diagnostic and prognostic tools. Recently, microRNAs are considered as a powerful biomarker in HIV-related studies [1-3]. So this short Commendatory will explain information about the role of micro RNAs in HIV related studies.A most recent study shows that cellular micro RNAs (miRNAs) can play crucial roles in controlling HIV-1 infection and replication.In addition, HIV-1 can manipulate the biogenesis of miRNAs as well as the expression profiles of cellular miRNAs [1]. It has been suggested that micro RNAs (miRNAs) contribute to the IFN-α-mediated suppression of HIV-1, moreover.